Kalaupapa National Historical Park and the legacy of Father Damien a pictorial history - Law, Anwei Skinsnes; Wisniewski, Richard A.; Goeas, Herbert (Honolulu, Hawaii Pacific Basin Enterprises, 1988)
"A condensed pictorial history of leprosy in Hawaii, from its introduction in the early 1800's, through its effects on the people whose lives were shaped by it, to the establishment of Kalaupapa as a national historical park."--Title page.
"Printed in Honolulu, Hawaii by: Pacific Printers, Inc."--Title page.
Includes bibliographical references (page 72)
Keywords: Missions to leprosy patients -- Hawaii -- History; Leprosy -- Hawaii -- History; Kalaupapa (Hawaii) -- History; Kalaupapa National Historical Park (Hawaii) -- History; Kalawao County (Hawaii) -- History